Folic acid-modified and functionalized CuS nanocrystal-based nanoparticles for combined tumor chemo- and photothermal therapy. (28th May 2017) - Zhu, Xiali; Zhang, Yingjie; Huang, Heqing; Zhang, Huijuan; Hou, Lin; Zhang, Zhenzhong
Abstract: Recent studies have identified that CuS nanocrystal (CuS NCs) could be used as a new class of promising photo-thermal agents due to their excellent plasmonic absorption abilities in a wide near-infrared (NIR) region. However, most of nanocarriers lack target capacity for combining chemotherapy and photothermal therapy effects. Herein, we reported chitosan (CS)-encapsulated and folic acid (FA)-modified nanoparticles (NPs) simultaneously loading with functionalized CuS NCs and docetaxel (DTX) (FA-DTX-PVP/CuS-NPs). Compared with free DTX, the photothermal agent CuS NCs and DTX not only could be specially targeted to deliver into MCF-7 cancer cells via a receptor-mediated endocytosis pathway, but also could be effectively transferred into tumor tissues of S180 tumor-bearing mice in vivo . More important, when combination with NIR laser irradiation, FA-DTX-PVP/CuS-NPs showed a higher antitumor efficacy than the individual therapies. Thus, as a remote and noninvasive tumor therapy strategy, these active targeting NPs may provide a great potential for tumor synergistic therapy.